The Archaeology of Cerro Guido and Sierra Baguales, Chile: Advances in the reconstruction of hunter-gatherer societies in steppe and mountain environments in northeastern Magallanes - Sierpe Gonzalez, Victor Manuel; Palacios, Cristobal; Martin, Fabiana Maria; Borrero, Luis Alberto; Arecheta, Constanza; Caravantes, Francisca (My University, 2024)
The results of the archaeological prospecting and surveys carried out in the area of Cerro Guido and Sierra Baguales are presented. The research covered four sectors between the north of the Las Chinas River and the area between the Las Flores stream and Palique outpost. Previous records indicate surface lithic evidence associated with the course of the Baguales River and the existence of "chenque" type burial sites at the top of Cerro Guido. During the surveys, 49 isolated surface finds, 23 concentrations of materials and 11 archaeological sites were recorded, three of them under rocky overhangs and eight in the open air. Of the latter, five correspond to large sites, suggesting a wider occupation of the territory by terrestrial hunter -gatherer groups. The test pits allowed a preliminary inference to the exploitation of terrestrial species and the supply of lithic raw materials upstream and/or to high altitude sectors near the Baguales mountain range. New dates extend the known chronology to c. 2500 BP. At the Las Flores Formation, the excavation of a rocky shelter revealed isolated and scattered human skeletal remains in an unusual context for the area, where previously only "chenque" burials had been recorded.
Keywords: archaeological exploration; raw materials; fauna exploitation; bioarchaeology; patagonia